Encapsulation of Magnetic Nanoparticles with Polymethyl methacrylate using a Simple Emulsion Solvent Evaporation - ไชยสัตย, อมร; เสือเอ็ง, สาวิตรี; ศิริวรรณ, ศิริวรรณ; เหมือนบาง, นพวรรณ; สะโจมแสง, วรายุทธ; ไชยสัตย์, ปรียาภรณ์ (Journal of Applied Research on Science and Technology (JARST), 2016)
In this research, a simple emulsion solvent evaporation technique was used to prepare the polymer capsule containing magnetic nanoparticles. The polymethyl methacrylate and iron (III) oxide (Fe2O3) were used as polymer shell and magnetic nanoparticles, respectively. The obtained capsules were thus coated with chitosan using glutaraldehyde as a crosslinker to connect chitosan chains presenting amino group on capsule surface. They would be applied in biosensor, protein separation and so on. It was found that the prepared capsules were spherical with the average diameter about 2 m. The zeta potential was approximately +36.60 mV due to the coating of chitosan.